Optimisasi Waktu Tempuh Pada Multi-AGV Menggunakan Particle Swarm Optimization - Anugrah Kusumo Pamosoaji (Jurnal Ilmiah Teknik Industri, 2016)
An algorithm for velocity planning on a continuous-curvature path of a pair of automated guided vehicles (AGVs) that minimizing its travelling time is presented. A class of 3-degree Bezier curves is used as basic form of the path. In addition, constraints of maximum allowable linear and radial accelerations are considered. The velocity plan algorithm is generated based on the characteristics of the path’s control points and maximum allowable radial velocity on some the path’s points. A set of properties of the allowable radial velocity is discussed. The verification of the new algorithm is revealed in the simulation results.